An IPM guide for enset root mealybug (Cataenococcus ensete) in enset production - Azerefegne, F.; Addis, T.; Alemu, T.; Lemawork, S.; Tadesse, E.; Gemu, M.; Blomme, Guy (2009)
This guide has been produced as an overview of a body of work that aims to help mitigate the threat of Enset mealybug: the biology and description of Enset mealybug; its behaviour; its geographical distribution; the pest symptoms; the list of mealybug dispersal methods, and the means of mealybug management, including prevention (clean planting material, extension, affordable management, quarantine, hygiene and ant control), cultural control (farmyard manure, hot water treatment, cultivation), biological control, use of insecticidal plant extracts (botanicals), and agrochemical control.